2011
DOI: 10.1038/cddis.2011.17
|View full text |Cite|
|
Sign up to set email alerts
|

IFN-γ signaling, with the synergistic contribution of TNF-α, mediates cell specific microglial and astroglial activation in experimental models of Parkinson's disease

Abstract: To through light on the mechanisms underlying the stimulation and persistence of glial cell activation in Parkinsonism, we investigate the function of IFN-γ and TNF-α in experimental models of Parkinson's disease and analyze their relation with local glial cell activation. It was found that IFN-γ and TNF-α remained higher over the years in the serum and CNS of chronic Parkinsonian macaques than in untreated animals, accompanied by sustained glial activation (microglia and astroglia) in the substantia nigra par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
182
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(203 citation statements)
references
References 41 publications
9
182
0
6
Order By: Relevance
“…In agreement with these results, other authors have shown that pharmacologic stimulation of D3R in human CD4 + T cells results in enhanced IFN-g production (33). Importantly, IFN-g has a critical role in stimulating and maintaining glial cell activation during PD, favoring chronic neuroinflammation (35). In contrast, WT and D3RKO CD4 + T cells display similar capability to acquire phenotypes Th17 or Tregs (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with these results, other authors have shown that pharmacologic stimulation of D3R in human CD4 + T cells results in enhanced IFN-g production (33). Importantly, IFN-g has a critical role in stimulating and maintaining glial cell activation during PD, favoring chronic neuroinflammation (35). In contrast, WT and D3RKO CD4 + T cells display similar capability to acquire phenotypes Th17 or Tregs (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, CD4 + T cells infiltrated into the CNS would be exposed to low DA levels, which would selectively stimulate D3R, thus promoting high production of IFN-g and TNF-a. These cytokines, in turn, would act synergistically over microglia favoring their activation and acquisition of the inflammatory phenotype M1 (35), specialized in secreting proinflammatory mediators, recruiting peripheral myeloid inflammatory cells, and thus promoting further destruction of DAergic neurons in the SN. Because a-synuclein aggregation or Lewy bodies formation, which contain oxidized CNS Ags, have been found in both drug-and genetically induced PD (5, 45), this working model would be applicable for drug-induced PD as well as for "spontaneous" genetically induced PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features were also observed in the brain of young drug addicts, who made use of the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) (Langston et al 1983), and in animal models of Parkinsonism, such as MPTP-injected mice and monkeys (Barnum and Tansey 2010;Walsh et al 2011). Increased levels of pro-inflammatory cytokines in both SN (Hunot et al 1996;Hirsh et al 1998;Barcia et al 2005Barcia et al , 2011 and cerebrospinal fluid (Nagatsu et al 2000;Pott Godoy et al 2008) of PD patients and animal models have also been described. The complexity of the immune response, however, does not allow to unequivocally establish whether reactive ''neuroglia'' contributes to DA neuron death.…”
Section: Introductionmentioning
confidence: 81%
“…On the other hand, the use of the chronic macaque model of MPTP administration is extremely important for a better understanding of the role of inflammatory processes in the longterm disease progression, more similar to what happens in humans. We had the opportunity to use sections of the striatum (both caudate and putamen) of previously studied macaques (Barcia et al 2004(Barcia et al , 2011. These samples were already well characterized for the loss of DA neurons and axons, as well as for microglia activation.…”
Section: Mmp-9 Immunolocalization and Quantitative Analysis In Contromentioning
confidence: 99%